Personality traits and level of motivation of TESL undergraduates towards ICT integration in L2 teaching - Loo, Kien Men; Noordin, Nooreen (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
In this robust digital age, the younger generations of students known as Digital Natives learn languages and other fields of knowledge via the use of technology. Many educational policies including the Malaysia Education Blueprint 2013-2025 have taken the initiatives to implement ICT in learning in bid to cater to the learning styles of the Digital Native students. However, reports have shown that the implementation process has not been smooth-sailing as majority of teachers have not been integrating ICT in their lessons seamlessly. Goldberg’s (1981) Big Five Model of Personality can explain various usage of ICT based on their respective trait but TESL undergraduates in the Malaysian context had not been studied before in the literature. In this study, the researcher purposively selected 72 TESL undergraduates from the Faculty of Educational Studies, Universiti Putra Malaysia to be involved in a quantitative study to investigate their personality traits and level of motivation in integrating ICT in their teaching practice. A questionnaire and semi-structured interview were used for data collection. The findings reported that their level of ICT integration in L2 teaching was high. Their level of motivation in integrating ICT in L2 teaching was also high. Next, the sample scored the highest in Openness to experience, followed by Conscientiousness, Agreeableness and Extraversion towards ICT integration in L2 teaching while low in Neuroticism. Using Pearson correlation, the findings showed that there was a statistically significant, moderate, positive relationship between their level of motivation, Agreeableness, Conscientiousness, Extraversion and Openness traits and their ICT integration in L2 teaching. These findings present vital implications for TESL program and course coordinators to facilitate their pre-service teachers to leverage ICT in their teaching practice.